Cover Image. (12th December 2018) - Cadoni, Enzo; Vanhara, Petr; Valletta, Elisa; Pinna, Elisabetta; Vascellari, Sarah; Caddeo, Graziano; Isaia, Francesco; Pani, Alessandra; Havel, Josef; Pivetta, Tiziana
Abstract : The front cover image is based on the Research Article MASS SPECTROMETRY DISCRIMINATION OF PHOSPHOLIPID PATTERNS IN CISPLATIN‐RESISTANT AND SENSITIVE CANCER CELLS by Enzo Cadoni et al., https://doi.org/10.1002/rcm.8320 .